Analyses of Supercontinuum Generation in Photonic Crystal Fibers - Noora Hussain Ali; Hassan Abid Yasser (University of Thi-Qar Journal, 2019)
In this work, the solid PCF are studied, where the solid core was surrounded by a number of holes with a diameter away from each other by distance. The strange behavior of dispersion with the presence of nonlinear phenomenon such as: self-phase modulation, self-steepening and stimulated Raman scattering allows the formation of higher order solitons in a short distance range . The study of SCG has been done by the numerical solution for the generalized propagation equation, where the Fourier transform method is used to solve the linear part and Runge-Kutta method to solve the nonlinear part. Higher order soliton means the possibility of soliton fission to the fundamental solitons and emissions the dispersive wave, this means the formation SCG. The SCG has been affected by each of: width, power and wavelength of the input pulses. On the other side, it is also affected by the fiber parameters and that in turn controls the zero dispersion wavelength , where the conditions and form bright soliton and dark soliton, respectively.